Multivalent Integrin-Specific Ligands Enhance Tissue Healing and Biomaterial Integration - Petrie, Timothy A. (2010)
Engineered biointerfaces covered with biomimetic motifs, including short bioadhesive ligands, are a promising material-based strategy for tissue repair in regenerative medicine. Potentially useful coating molecules are ligands for the integrins, major extracellular matrix receptors that require both ligand binding and nanoscale clustering for maximal signaling efficiency. We prepared coatings consisting of well-defined multimer constructs with a precise number of recombinant fragments of fibronectin (monomer, dimer, tetramer, and pentamer) to assess how nanoscale ligand clustering affects integrin binding, stem cell responses, tissue healing, and biomaterial integration. Clinical-grade titanium was grafted with polymer brushes that presented monomers, dimers, trimers, or pentamers of the α(5)β(1) integrin–specific fibronectin III (7 to 10) domain (FNIII(7–10)). Coatings consisting of trimers and pentamers enhanced integrin-mediated adhesion in vitro, osteogenic signaling, and differentiation in human mesenchymal stem cells more than did surfaces presenting monomers and dimers. Furthermore, ligand clustering promoted bone formation and functional integration of the implant into bone in rat tibiae. This study establishes that a material-based strategy in which implants are coated with clustered bioadhesive ligands can promote robust implant-tissue integration.